2017
DOI: 10.5455/medarh.2017.71.280-283
|View full text |Cite
|
Sign up to set email alerts
|

Difference Between Cryotherapy and Follow Up Low Grade Squamous Lesion of Cervix Uteri

Abstract: Introduction:Cervical cancer can be successfully prevented by effective treatment.Aim:Analyse of success of cryotherapy in LSIL and ASCUS.Materials et methods:In retrospective study between January 2016 to March 2017, 3244 PAP test were analysed. 257 patients who had been diagnosed with LSIL and ASCUS from PAP smear were divided in two groups: women who had HPV positive, colposcopic positive and cytologic finding of LSIL or ASCUS treathed with cryotherapy and women with LSIL, ASCUS and negative colposcopy. χ2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…Abnormal colposcopic findings in HSIL lesions were found in 72.9% (N-69) and in ASC-H lesions in 40.5% (N-15). Colposcopic examination has better results in differentiating high-grade lesions from lower-grade lesions and correlates with direct biopsy and is described as the gold standard in the diagnosis of precancerous lesions ( 12 , 13 , 14 ), as shown by our study. Colposcopy showed better sensitivity in this study in 72,9% (N-69) compared to cytology which showed 67.7% (N-55).…”
Section: Discussionsupporting
confidence: 65%
“…Abnormal colposcopic findings in HSIL lesions were found in 72.9% (N-69) and in ASC-H lesions in 40.5% (N-15). Colposcopic examination has better results in differentiating high-grade lesions from lower-grade lesions and correlates with direct biopsy and is described as the gold standard in the diagnosis of precancerous lesions ( 12 , 13 , 14 ), as shown by our study. Colposcopy showed better sensitivity in this study in 72,9% (N-69) compared to cytology which showed 67.7% (N-55).…”
Section: Discussionsupporting
confidence: 65%
“…Four weeks after the treatment, epithelisation of cervix was found in 87,40%, and after 6 weeks in 93,50%. In similar research of efficiency of cryotherapy, Jahic finds efficiency in 89,3%, Peck in 91%, Alvarez in 92%, Gay in 95% while the Alliance for prevention of cervical cancer confirmed that the efficiency of cryotherapy in women with cervical intraepithelial lesion is 98,5% (6).…”
Section: Discussionmentioning
confidence: 91%
“…The percentage of representation of HPV is significantly more frequent in HSIL (90% to 100%). Untreated LSIL can progress in 13% of cases to HSIL during 2 years of monitoring ( 9 , 10 ). Women infected with HPV 16 have a transition of LSIL into HSIL in 9% of cases.…”
Section: Discussionmentioning
confidence: 99%